Building of the model of psychological characteristic of the rescuer while being on duty or in the process of emergency situations - Burminski Дмитрий Анатольевич; Kadol Федор Владимирович (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
With the help of questionnaire the investigation of psychological factors having influence on the activity of personnel of Gomel department for emergency situations was conducted. On the base of the analysis of the personnel’s answers was built the model of psychological characteristics of the activity of rescuer while being on the duty or in the process of liquidation of emergency situations. A number of tasks, raising in the level of psychological readings and reducing the probability of accidents during the service, were formulated for the leaders of the departments.